IMPLEMENTATION OF CHARACTER EDUCATION STRENGTHENING IN ONLINE LEARNING DURING COVID-19 PANDEMIC AT MADRASAH IBTIDAIYAH - Ragil Dian Purnama Putri; Shopyan Jepri Kurniawan; Muqowim Muqowim (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The COVID-19 pandemic is still ongoing. It has an impact on the implementation of education so in Indonesia, it is necessary to implement Learning from Home. As a result, the Character Education Strengthening (PPK) learning model at Madrasah cannot run optimally. This paper is written to see what extent of the implementation of strengthening character education in online learning during the COVID-19 pandemic at Madrasah Ibtidaiyah Grojogan. The writing method used is a descriptive qualitative approach. The research subjects involved principals, classroom teachers, and parents/family members. Meanwhile, data collection uses observation, interviews, and documentation. Subsequently, the analysis process uses data collection in the research field, reduction, presentation, and drawing conclusions. The research results indicate that the implementation of character education strengthening at MI Grojogan has been conducted through collaboration with students' parents/family members. Based on its implementation, the school face their own challenges, either challenges from the education unit or challenges from the family. The character education strengthening applied in online learning includes five values, they are religious, nationalist, independent, mutual cooperation, and integrity.